Synthesis and characterization of organoclay from sodium montmorillonite and fatty hydroxamic acids - Hoidy, Wisam H.; Ahmad @ Ayob, Mansor; Al-Mulla, Emad A. Jaffar; Ibrahim, Nor Azowa (Science Publications, 2009)
Problem statement: Sodium Montmorillonite (Na-MMT) has been modified via cation exchange reaction using Fatty Hydroxamic Acids (FHAs) synthesized from palm oil as a surfactant to produce organoclay which is used to prepare polymer nanocomposites.